Repertoire Construction for Critical Cross-Cultural Literacy of English Majors: Based on the Research Paradigm of Systemic Functional Linguistics - Zhao, Ran; Lu, Danyun (Frontiers in Psychology, 2022)
The ambiguous development trend of cultural globalization brings both opportunities and challenges to China’s cultural development. English major in colleges and universities, a discipline of cross-cultural education, should look at the cultural communication of the target country dialectically based on the national consciousness of the home country. At present, the education related to cross-cultural communication of English majors in colleges and universities usually aims at literacy such as individual cross-cultural competence, cross-cultural awareness and critical thinking of teaching objects, which are important components of the cross-cultural meaning system. Therefore, all these are collectively referred to as critical cross-cultural literacy (CCCL). On the basis of the research paradigm of systemic functional linguistics (SFL), the identities of textbook authors were “identified” and the corresponding discourse strategies were analyzed from an individualized perspective in this research with the appraisal system as a semantic framework, thus guiding students to “realize” the construction and improvement of repertoire by learning evaluation strategies and selecting individual identities.